Penerapan Metode Total Productive Maintenance Dengan Overall Equipment Effectiveness (OEE) Pada Mesin Grinding di PT. VPRK - Putra, Abrardy Firlana; Kusnadi, Kusnadi (Fakultas Teknik Universitas Tulang Bawang, 2024)
This research focuses on analyzing the implementation “of Total Productive Maintenance (TPM)” at PT. VPRK “by” utilizing “Overall Equipment Effectiveness (OEE) as an indicator” to assess “the” performance of grinding machines at PT. VPRK. The aim of the research is to evaluate the effectiveness and efficiency of the machine by identifying inhibiting factors that influence the performance of the grinding machine. The TPM method is applied to increase availability, quality and overall machine performance. OEE is used as a critical measuring tool to assess productivity and operational efficiency. The research results show that the OEE value of grinding machines in the January 2023 period is 79.78%. This value is not in accordance with the world-class OEE value standard, which is 85%. The biggest factor that influences the low OEE value is because the machine downtime is quite high, which affects the machine availability value so the machine availability value is 81.16%. Keywords: Maintenance, Overall Equipment Effectiveness, Total Productive Maintenance